2020
DOI: 10.3389/fmed.2020.607821
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Risk-Stratification Models of the High-Flow Nasal Cannula Therapy in COVID-19 Patients With Hypoxemic Respiratory Failure

Abstract: Background: High-flow nasal cannula (HFNC) has been recommended as a suitable choice for the management of coronavirus disease 2019 (COVID-19) patients with acute hypoxemic respiratory failure before mechanical ventilation (MV); however, delaying MV with HFNC therapy is still a dilemma between the technique and clinical management during the ongoing pandemic.Methods: Retrospective analysis of COVID-19 patients treated with HFNC therapy from four hospitals of Wuhan, China. Demographic information and clinical v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 40 publications
4
47
1
1
Order By: Relevance
“…Several studies have reported the use of HFNC in COVID-19 patients (Geng et al, 2020;Wang et al, 2020;Chandel et al, 2020;Hu et al, 2020;Xu et al, 2020a). These studies showed that the rates of HFNC failure were between 38 and 45%, which agreed with the failure rate in our study (44%).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Several studies have reported the use of HFNC in COVID-19 patients (Geng et al, 2020;Wang et al, 2020;Chandel et al, 2020;Hu et al, 2020;Xu et al, 2020a). These studies showed that the rates of HFNC failure were between 38 and 45%, which agreed with the failure rate in our study (44%).…”
Section: Discussionsupporting
confidence: 91%
“…As the variables required to calculate the ROX index are easy to obtain, even in the resourcelimited area, it may be helpful for the physicians to early identify patients with a high likelihood of success and those who will require escalation therapy. Apart from the ROX index, the advanced age, increased SOFA score, and decreased platelets were also reported to be associated with increased HFNC failure (Hu et al, 2020;Xu et al, 2020a). As such, the combined use of these variables and the ROX index might help improve the predictive accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…These side effects are comparable with those under conventional oxygen devices: mask discomfort, nasal, and oral dryness, eye irritation, nasal and eye trauma, bronchoconstriction, and gastric distention [8]. Few studies have focused on the impact of HFNCO in older patients [9][10][11], and, to the best of our knowledge, only one of them studied the impact of HFNCO during SARS-CoV-2 ARF [10]. However, this study was observational with no comparison group.…”
Section: Introductionmentioning
confidence: 84%
“…APACHE II and PSI scores can be used to determine when intubation is needed so that it is not late. 20…”
Section: Discussionmentioning
confidence: 99%